Mapping Competences of the Technological Interface Centers to Support the Transition of Portuguese Companies Toward the Circular Economy - Ferreira, Luís; Matias, Rita (Frontiers in Sustainability, 2021)
This research paper is part of an investigation about the national competences in the field of Circular Economy (CE) within the so-called technological infrastructures. The purpose was to map these competences among the Technological Interface Centers (CIT) to support Portuguese companies in the transition to a more circular economy. A survey was designed under a general principle that all types of competences should have a straight contribution to the circular strategies included in the Portuguese Circular Economy Action Plan. Four main domains of competences were surveyed: “Guidance and Awareness”; “Eco-design”; “Resource Efficiency” and “Industrial Symbiosis”. It was possible to ascertain CE competences profiles for the three groups of CIT (Technological Centers, Technology Transfer Centers and Institutes of New Technologies) and recognize different and characteristic profiles of competences. Technological Centers have characteristic competences in all four domains, with greater emphasis on “Eco-design” and “Resource Efficiency”. Technology Transfer Centers also have characteristic competences in the four domains; however, its offer is more distributed, with no particular intensity noted in any specific domain. Institutes of New Technologies only present characteristic competences in “Eco-design”. Gaps identified in the “Guidance and Awareness” domain are “self-diagnosis tools for the efficient use of resources” and “maturity assessment tools in Circular Economy”. In the domain of “Eco-design” the only gap is the “skills to assist in the implementation of circular business models”. “Databases with examples of good practices for resource efficiency” and the “human resources and tools capable of carrying out energy and materiel audits” are the major gaps in the domain of “Resource Efficiency”. Finally, the “network of specialists with technical and commercial knowledge that enhances the use of by-products and residues in industry” and the “technical capacity or means to mediate the transfer of waste and by-product flows between industrial processes” are gaps in the domain of “Industrial Symbiosis”. A characterization sheet for each CIT was set up with the competences’ makeup of every CIT structured. The business community in Portugal will be able to identify, in an objective way, competences that might be useful in the process of adapting their businesses towards more circular models.